LOCAL GOVERNMENT MANAGEMENT OF HEALTH CRISES: A SYSTEMATIC REVIEW OF RESPONSES AND SUCCESSES - Meilinda, Selvi Diana (INDONESIAN GOVERNANCE JOURNAL : KAJIAN POLITIK-PEMERINTAHAN, 2025)
This research aims to explain how local governments face challenges in managing health crises, where local governments must be able to manage health crises effectively to maintain public health and minimize negative impacts. The method used in this research is a systematic literature review with a qualitative approach, by obtaining data sources from various articles, forums or other studies. The results of the discussion from this research state that one form of health crisis management by local governments is realized by mobilizing health workers, which is an effort to meet the needs of health workers in serving health crises that occur in the community. Apart from that, the government needs to increase capacity as a form of health crisis mitigation and preparedness which aims to increase the capacity of officers in responding to health crises that occur. as examples of capacity building activities carried out are the Health Crisis Management Information System (SIPKK), Rapid Health Assessment (RHA), Emergency Medical Team (EMT), logistics management, Table Top Exercise (TTx), and Contingency Plans